Removal of Pb(II) from Aqueous Solution Using Tremolite Amianthus - Peng, Ge; Wan, Lijuan; Wang, Lixia (Asian Journal of Chemistry, 2012)
Tremolite amianthus was characterized and studied for the removal of Pb2+ from aqueous solution through batch equilibrium experiments. Scanning electron microscope (SEM) was used to observe the surface properties of the tremolite amianthus. To highlight their application, selected information on time, pH, initial metal concentration and adsorption capacity of tremolite amianthus are investigated. Adsorption behavior of Pb2+ ions was described with the Langmuir and Freundlich equations. The adsorption capacity of tremolite amianthus for Pb2+ was determined from the isotherms equations at different temperature. The thermodynamic parameters (DGº, DHº and DSº) were also determined and the adsorption process is more favoured at lower temperatures.